The Tourist Perception Toward Central Market in Malaysia - Yunesa, Vitra; Ab Rahim, Nur Atirah Binti (Sumatra Journal of Disaster, Geography and Geography Education, 2018)
The purpose of this research is to describe tourist perception toward Central Market in Malaysia, in terms of tourist perception toward Central Market existence, tourist perception toward shopping security in the Central Market, and tourist perception toward shopping convenience in the Central Market. This research employs descriptive qualitative method. Data were collected through observation, interview, and documentation study. Data were analysed by using data reduction stage, data presentation, and drawing conclusion. Research results were 1) Tourist perception toward the existence of Central Market was Central Market as a historical market, Malaysian culinary and souvenir shopping centre, 2) Tourist perception toward shopping security were security official, Security Counter, CCTV and security facilities. 3) Tourist perception toward convenience in the term of facility to facilitate tourist to shop.